2020
DOI: 10.1093/jpids/piaa165
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus-2 Pneumonia in a Newborn Treated With Remdesivir and Coronavirus Disease 2019 Convalescent Plasma

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is a novel pandemic virus. Mounting evidence supports the possibility of vertical transmission, which at the present time appears to be rare. We report a newborn with vertically acquired SARS-CoV-2 who developed acute respiratory failure and received remdesivir and coronavirus disease 2019 convalescent plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Currently, only a limited number of case reports and case series have been published on the use of COVID-19 convalescent plasma in children (18)(19)(20)(21)(22)(23)(24)(25)(26) and a detailed pharmacokinetic analysis is lacking. In this prospective study, high-titer convalescent plasma appears to be safe when given to high-risk children.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, only a limited number of case reports and case series have been published on the use of COVID-19 convalescent plasma in children (18)(19)(20)(21)(22)(23)(24)(25)(26) and a detailed pharmacokinetic analysis is lacking. In this prospective study, high-titer convalescent plasma appears to be safe when given to high-risk children.…”
Section: Discussionmentioning
confidence: 99%
“…12 Except the report by Goldman et al, 25 there are only a few case reports of children with COVID-19 treated with remdesivir. 26 27 28 29 Remdesivir became available for use in July 2020 in Korea. To our knowledge, no pediatric case of severe COVID-19 treated with remdesivir has been reported in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Citations of newborn infection have emerged on the basis of positive findings of viral RNA [21,32,34,40,52,76,94,95,127,136,152,218,227,245,[256][257][258][259][260]. As for maternal infections, viral RNA may be detected for a considerable period of time after infection onset [260].…”
Section: Neonatal Infectionsmentioning
confidence: 99%
“…It was not clear whether respiratory distress was solely attributable to COVID-19 in the latter report given the degree of prematurity. Hopwood et al found a term newborn to be seemingly infected in the first 25 h of life and decompensation included severe respiratory failure [257]. The mother may have had ruptured membranes for several days prior to vaginal delivery.…”
Section: Neonatal Infectionsmentioning
confidence: 99%